2022
DOI: 10.3390/s22145387
|View full text |Cite
|
Sign up to set email alerts
|

Feedforward Control of Piezoelectric Ceramic Actuators Based on PEA-RNN

Abstract: Multilayer perceptron (MLP) has been demonstrated to implement feedforward control of the piezoelectric actuator (PEA). To further improve the control accuracy of the neural network, reduce the training time, and explore the possibility of online model updating, a novel recurrent neural network named PEA-RNN is established in this paper. PEA-RNN is a three-input, one-output neural network, including one gated recurrent unit (GRU) layer, seven linear layers, and one residual connection in the linear layers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…PEA actuator (T434-A4-201, Piezo Systems, Inc., Cambridge, MA, USA) 0.62 RNN [25] The feedforward compensator was developed by the deep learning method (RNN).…”
Section: Comparison With Other Relevant Workmentioning
confidence: 99%
See 2 more Smart Citations
“…PEA actuator (T434-A4-201, Piezo Systems, Inc., Cambridge, MA, USA) 0.62 RNN [25] The feedforward compensator was developed by the deep learning method (RNN).…”
Section: Comparison With Other Relevant Workmentioning
confidence: 99%
“…The results are shown in Table 6 , where we can see that our method improves tracking performance on nanopositioning systems and outperforms in comparison with the other methods in terms of average RMSE. The compensation method that is based only on the improved inverse Preisach [ 52 ] method has low accuracy (RMSE of =0.15 μm), but it is better than the compensation method based on the recurrent neural networks (RNNs) [ 25 ], which produced an average RMSE of 0.465 μm. The FF-FB control method based on the LSSVM algorithm without modeling hysteresis [ 28 ] produced the highest RMSE value (0.62 μm).…”
Section: Comparison With Other Relevant Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The only factor affecting the model output in the rate-independent method is the amplitude of the input voltage. The major benefit of these models is that they are easy to identify and simple to implement [ 22 , 23 ]. Within this method, three different model theories can be distinguished: (1) the theory of dynamic modeling, which is represented mathematically by a collection of differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…A hysteresis model-based approach is primarily used [20,21]. It has been shown that Prandtl-Ishlinskii(PI) hysteresis modeling is one method often used to describe hysteresis [22], and it typically describes a continuous loop of hysteresis that is rateindependent [23]. This PI hysteresis modeling has the advantage of being simple, and its hysteresis compensator can be calculated analytically [24].…”
Section: Introductionmentioning
confidence: 99%